The Share of Top Wealth-Holders in National Wealth, 1922-1956. - Bierman, Harold; Lampman, Robert J. (Journal of Finance, 1962)
Based largely upon data derived from federal estate tax returns, this report investigates the distribution of wealth in the United States in the years 1922-56, and finds important changes in the degree of economic inequality. More than 100 tables and 37 charts illustrate the author's findings.